PEMBELAJARAN PENEMUAN TERBIMBING PADA MATA KULIAH IPA GUNA MENINGKATKAN KETERAMPILAN DASAR MENELITI BAGI MAHASISWA PGSD - Kartono, Kartono (Jurnal Inovasi Pendidikan, 2010)
This research was aimed at finding out the influence of constructivism learning on: (1) the increase in concept understanding, and (2) the increase in science process skill of PGSD students. The research method applied was classroom action research. The research is conducted in three cycles and each cycle comprises planning, action imple-mentation, observation, and reflecting/evaluation. The subject of this research is the third semester of PGSD students of FKIP UNS, consisting of 42 students. The length of the research is six months from July to December 2008. Based on the analysis, it can be concluded that constructivism learning can increase the third semester students of PGSD dealing with (1) science concepts understanding and (2) science process skills.